Invisible actors: Web application programming interfaces, television, and social media - Lahey, Michael (Convergence (London, England), 2016)
This article focuses on the role web application programming interfaces (APIs) play in the television (TV) industry’s social media efforts. Web APIs are coding interfaces that allow different databases of information to communicate with one another. The widespread implementation of web APIs as a standard for information sharing offers a way for TV companies to more easily cobble together a presence in connected viewing environments. In this light, web API acts as, what Joshua Braun calls, ‘transparent intermediaries’ that actively shape the range of possibilities available in these types of intermedial partnerships. I explain web APIs before showing how they relate to media studies through the TV show Psych’s forays into designing social media experiences. Additionally, I will explain how web API-connected digital environments are used to facilitate what Tiziana Terranova calls soft control as web APIs embody Web 2.0 ideologies that celebrate information sharing between businesses that track audience attention.